Flame retardant ceramic silicone rubber and preparation method thereof

By functionalizing the carbon nanotubes and combining other fillers, silicon rubber composite materials with excellent flame retardant and ceramicized properties were prepared, which solved the problem of flammability of existing ceramicized silicon rubber materials and achieved higher flame retardant properties.

CN116554692BActive Publication Date: 2025-03-04ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310669809.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-03-04
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

The existing ceramicized silicone rubber materials have limited their application in areas with high flame retardant requirements due to their inherent flammability.

Method used

Functionalized carbon nanotubes are prepared by carboxylation and sodium phytate complexing, and used as flame retardant and catalyst, combined with fillers such as glass powder and wollastonite, and added to silicone rubber to prepare flame retardant ceramicized silicone rubber composite material.

Benefits of technology

The flame retardant and ceramicization properties of silicone rubber composite materials are significantly improved, forming a denser carbon layer, enhancing the thermal stability and free radical suppression ability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004272449800000031
    Figure BDA0004272449800000031
  • Figure BDA0004272449800000051
    Figure BDA0004272449800000051
  • Figure BDA0004272449800000061
    Figure BDA0004272449800000061
Patent Text Reader

Abstract

The invention discloses a flame retardant ceramic silicone rubber and a preparation method thereof, comprising the following raw materials by weight: 100 parts of silicone rubber, 30-40 parts of white carbon black, 1-2 parts of dicumyl peroxide, 20-30 parts of wollastonite, 30-40 parts of low melting point glass powder, 5-7 parts of hydroxy silicone oil, and 1-5 parts of functionalized carbon nanotubes. The invention first carboxylates carbon nanotubes, then forms a complex with phytic acid and carboxylated carbon nanotubes by doping cobalt and copper ions, prepares green and environmentally friendly functionalized carbon nanotubes, uses them as flame retardants and catalysts, selects glass powder as a flux, and wollastonite as a ceramic filler, and successfully prepares a silicone rubber composite material with excellent flame retardant ceramic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of flame retardant and ceramic materials, and specifically relates to a flame retardant ceramic silicone rubber and a preparation method thereof. Background Art

[0002] Silicone rubber (SR) has excellent high and low temperature resistance, weather resistance and ozone resistance, so it is used in many fields, including aviation, aerospace industry, electronics and health care. Ceramic silicone rubber (CSR) is a new type of refractory material with a relatively simple preparation process. It only needs to add ceramic fillers, vulcanizers and fluxing agents to silicone rubber, and then simply blend them to prepare CSR composite materials. However, the inherent flammability of CSR limits its wider application, especially in fields with high flame retardancy requirements. Therefore, it is of great significance to study silicone rubber composite materials with flame retardant and ceramic properties.

[0003] As a one-dimensional nanomaterial, carbon nanotubes are light in weight, have perfectly connected hexagonal structures, and have many exceptional mechanical, electrical, and chemical properties. Carbon nanotubes have good thermal stability and can increase the density of the carbon layer by playing a good physical barrier role, so they have certain flame retardant properties. However, the flame retardant efficiency of unmodified carbon nanotubes is low, so in order to improve the flame retardant efficiency of carbon nanotubes, surface modification becomes very important. Summary of the invention

[0004] The purpose of the present invention is to develop a flame retardant ceramic silicone rubber. Functionalized carbon nanotubes are prepared and used as flame retardants and catalysts. Glass powder is selected as a flux and wollastonite is selected as a ceramic filler. These are added together with other fillers into silicone rubber to obtain a silicone rubber composite material with excellent flame retardant and ceramic properties.

[0005] To achieve the purpose, the present invention adopts the following technical solution:

[0006] A flame retardant ceramic silicone rubber comprises the following raw materials in parts by weight: 100 parts of silicone rubber, 30-40 parts of white carbon black, 1-2 parts of dicumyl peroxide (DCP), 20-30 parts of wollastonite, 30-40 parts of low-melting-point glass powder, 5-7 parts of hydroxy silicone oil and 1-5 parts of functionalized carbon nanotubes.

[0007] Furthermore, the preparation method of the functionalized carbon nanotubes is: firstly, carbon nanotubes are carboxylated to obtain carboxylated carbon nanotubes; then sodium phytate and carboxylated carbon nanotubes are doped with cobalt and copper ions to form a complex to obtain functionalized carbon nanotubes. The specific preparation steps are:

[0008] (1) Preparation of carboxylated carbon nanotubes:

[0009] After the concentrated sulfuric acid and concentrated nitric acid are mixed, the carbon nanotubes are added and ultrasonicated until uniformly dispersed, and then placed in a 100-120°C oil bath for heating and reflux reaction for 12-15 hours; after the reaction, an appropriate amount of deionized water is added for dilution, and a black viscous substance is obtained by centrifugation, and then carboxylated carbon nanotubes are obtained after washing and drying;

[0010] (2) Preparation of functionalized carbon nanotubes:

[0011] Sodium phytate and carboxylated carbon nanotubes are dissolved in distilled water by ultrasound, and then a mixed solution of cobalt nitrate hexahydrate and copper nitrate is added, and the mixture is transferred to a reactor and reacted at 200-300° C. for 8-12 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed and dried to obtain functionalized carbon nanotubes.

[0012] Furthermore, in step (1), the mass concentration of concentrated sulfuric acid is 90-98%, the mass concentration of concentrated nitric acid is 60-68%, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1-2:3-4.

[0013] Furthermore, in step (2), the dosage ratio of sodium phytate, carboxylated carbon nanotubes, distilled water, cobalt nitrate hexahydrate and copper nitrate is 4-5 g: 4-5 g: 50-60 mL: 100-120 mL, the total molar amount of cobalt nitrate hexahydrate and copper nitrate in the mixed solution is 26.4 mmol, and the molar ratio of cobalt nitrate hexahydrate to copper nitrate is 1-2: 1-2.

[0014] Furthermore, the silicone rubber is methyl vinyl silicone rubber.

[0015] The preparation method of the flame-retardant ceramic silicone rubber of the present invention is as follows: silicone rubber, white carbon black, wollastonite, low-melting-point glass powder, hydroxy silicone oil, dicumyl peroxide and functionalized carbon nanotubes are sequentially added to an internal mixer, mixed evenly, pressed into sheets in an open mixer, and vulcanized with a flat vulcanizer; the vulcanized sample is placed in a muffle furnace and calcined at 800-1000° C. for 1-2 hours to prepare the flame-retardant ceramic silicone rubber. The vulcanization conditions are: temperature 170° C., pressure 5-7 MPa, and time 18-25 minutes.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] The present invention first carboxylates carbon nanotubes, and then forms a complex between phytic acid and carboxylated carbon nanotubes by doping cobalt and copper ions to prepare green and environmentally friendly functionalized carbon nanotubes. The present invention further selects functionalized carbon nanotubes as flame retardants and catalysts to improve the flame retardant properties of ceramic silicone rubber, selects glass powder as a flux, and wollastonite as a ceramic filler, and successfully prepares a flame retardant ceramic silicone rubber composite material. The functionalized carbon nanotubes obtained by the present invention: on the one hand, have high thermal stability, which can improve the thermal stability of the rubber composite material; on the other hand, they will generate phosphorus-containing compounds and metal oxides that are beneficial to inhibiting free radicals. The metal oxides have a catalytic effect and can promote Si-CH in silicone rubber. 3 The fracture of the carbon atoms and the coupling of free radicals form a Si-C-Si cross-linked structure and a denser carbon layer, thereby improving the flame retardant properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 (A) and (B) are the HRR curves and THR curves of sample 4, sample 5 and sample 6 respectively. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the embodiments.

[0020] Example 1

[0021] This embodiment prepares the silicone rubber composite material according to the following steps:

[0022] 1. Preparation of functionalized carbon nanotubes

[0023] (1) Preparation of carboxylated carbon nanotubes:

[0024] 50 mL of 98% concentrated sulfuric acid and 150 mL of 68% concentrated nitric acid were added to a beaker, and then 5 g of CNTs powder was added and ultrasonicated until uniformly dispersed to obtain a black viscous liquid. The ultrasonicated liquid was placed in a 100°C oil bath and heated under reflux for 15 hours; after the reaction, an appropriate amount of deionized water was added for dilution, and a black viscous substance was obtained by centrifugation, and then carboxylated carbon nanotubes were obtained after washing and drying.

[0025] (2) Preparation of functionalized carbon nanotubes:

[0026] 4 g of sodium phytate and 4 g of carboxylated carbon nanotubes were dissolved in 50 mL of distilled water by ultrasound, and then 100 mL of a mixed solution of cobalt nitrate hexahydrate and copper nitrate was added (the total molar amount of cobalt nitrate hexahydrate and copper nitrate was 26.4 mmol, and the molar ratio of cobalt nitrate hexahydrate to copper nitrate was 1:1), and the mixture was transferred to a 150 mL reactor and reacted at 200 ° C for 12 h; after the reaction was completed, it was cooled to room temperature, centrifuged, washed and dried to obtain black functionalized carbon nanotubes.

[0027] 2. Preparation of silicone rubber composite materials

[0028] According to the sample formula in Table 1, silicone rubber, white carbon black, wollastonite, low melting point glass powder, hydroxy silicone oil, DCP and functionalized carbon nanotubes were added to the internal mixer in sequence, mixed evenly, pressed into sheets in an open mixer, and vulcanized with a flat vulcanizer under the following conditions: temperature 170°C, pressure 5MPa, time 25min. The vulcanized sample was placed in a muffle furnace and calcined at 800°C for 2h to prepare a flame-retardant ceramic silicone rubber.

[0029] Table 1 Formula of Sample 1, Sample 2 and Sample 3 (parts by weight)

[0030] Sample name / mass Sample 1 Sample 2 Sample 3 Silicone Rubber 100 100 100 White Carbon Black 30 30 30 Wollastonite 0 20 20 Low melting point glass powder 0 30 30 Hydroxy silicone oil 0 5 5 DCP 1 1 1 Functionalized carbon nanotubes 0 0 1

[0031] The following performance tests were conducted on the rubber composite material: the tensile strength at break and the elongation at break were tested in accordance with GB / T528-2009 and GB / T529-200, respectively; the standard bending strength of the ceramic body was tested in accordance with GB / T 1449-2005; and the limiting oxygen index test was tested in accordance with ASTM D2863. Table 2 shows the limiting oxygen index LOI, ceramic body bending strength, tensile strength at break, and elongation at break of sample 1, sample 2, and sample 3. It can be seen that the silicone rubber composite material prepared by the present invention has excellent flame retardant properties and ceramic properties.

[0032] Table 2 Performance test data of sample 1, sample 2 and sample 3

[0033]

[0034] Example 2

[0035] This embodiment prepares the silicone rubber composite material according to the following steps:

[0036] 1. Preparation of functionalized carbon nanotubes

[0037] (1) Preparation of carboxylated carbon nanotubes:

[0038] 50 mL of 98% concentrated sulfuric acid and 150 mL of 68% concentrated nitric acid were added to a beaker, and then 5 g of CNTs powder was added and ultrasonicated until uniformly dispersed to obtain a black viscous liquid. The ultrasonicated liquid was placed in a 110°C oil bath and heated under reflux for 13 hours; after the reaction, an appropriate amount of deionized water was added for dilution, and a black viscous substance was obtained by centrifugation, and then carboxylated carbon nanotubes were obtained after washing and drying.

[0039] (2) Preparation of functionalized carbon nanotubes:

[0040] 4.5 g of sodium phytate and 4.5 g of carboxylated carbon nanotubes were dissolved in 55 mL of distilled water by ultrasound, and then 110 mL of a mixed solution of cobalt nitrate hexahydrate and copper nitrate was added (the total molar amount of cobalt nitrate hexahydrate and copper nitrate was 26.4 mmol, and the molar ratio of cobalt nitrate hexahydrate to copper nitrate was 1:1), and the mixture was transferred to a 150 mL reactor and reacted at 250 ° C for 10 h; after the reaction was completed, it was cooled to room temperature, centrifuged, washed and dried to obtain black functionalized carbon nanotubes.

[0041] 2. Preparation of silicone rubber composite materials

[0042] According to the sample formula in Table 3, silicone rubber, white carbon black, wollastonite, low melting point glass powder, hydroxy silicone oil, DCP and functionalized carbon nanotubes were added to the internal mixer in sequence, mixed evenly, pressed into sheets in an open mixer, and vulcanized with a flat vulcanizer under the following conditions: temperature 170°C, pressure 6MPa, time 21min. The vulcanized sample was placed in a muffle furnace and calcined at 950°C for 1.5h to prepare a flame-retardant ceramic silicone rubber.

[0043] Table 3 Formula of Sample 4, Sample 5 and Sample 6 (parts by weight)

[0044] Sample name / mass Sample 4 Sample 5 Sample 6 Silicone Rubber 100 100 100 White Carbon Black 35 35 35 Wollastonite 0 25 25 Low melting point glass powder 0 35 35 Hydroxy silicone oil 0 6 6 DCP 1.5 1.5 1.5 Functionalized carbon nanotubes 0 0 3

[0045] The following performance tests were conducted on the rubber composite materials: The heat release test of the samples was conducted using a cone calorimeter model JCZ-2 from Suzhou Zhengbiao Analytical Instrument Co., Ltd. in accordance with ISO5660-1:2002 standard. The specimen size was 130×13×3mm 3 ; The tensile strength at break and elongation at break were tested in accordance with GB / T528-2009 and GB / T529-200, respectively; the standard bending strength of the ceramic body was tested in accordance with GB / T 1449-2005; the limiting oxygen index test was tested in accordance with ASTMD2863. Table 4 shows the peak heat release (pHRR), total heat release (THR), limiting oxygen index LOI, ceramic body bending strength, tensile strength at break, and elongation at break of sample 4, sample 5, and sample 6. It can be seen that the silicone rubber composite material prepared by the present invention has excellent flame retardant properties and ceramic properties.

[0046] Table 4 Performance test data of sample 4, sample 5 and sample 6

[0047]

[0048] Example 3

[0049] This embodiment prepares the silicone rubber composite material according to the following steps:

[0050] 1. Preparation of functionalized carbon nanotubes

[0051] (1) Preparation of carboxylated carbon nanotubes:

[0052] 50 mL of 98% concentrated sulfuric acid and 150 mL of 68% concentrated nitric acid were added to a beaker, and then 5 g of CNTs powder was added and ultrasonicated until uniformly dispersed to obtain a black viscous liquid. The ultrasonicated liquid was placed in a 120°C oil bath and heated under reflux for 12 hours; after the reaction, an appropriate amount of deionized water was added for dilution, and a black viscous substance was obtained by centrifugation, and then carboxylated carbon nanotubes were obtained after washing and drying.

[0053] (2) Preparation of functionalized carbon nanotubes:

[0054] 5 g of sodium phytate and 5 g of carboxylated carbon nanotubes were dissolved in 60 mL of distilled water by ultrasound, and then 120 mL of a mixed solution of cobalt nitrate hexahydrate and copper nitrate was added (the total molar amount of cobalt nitrate hexahydrate and copper nitrate was 26.4 mmol, and the molar ratio of cobalt nitrate hexahydrate to copper nitrate was 1:1), and the mixture was transferred to a 150 mL reactor and reacted at 800 ° C for 8 h; after the reaction was completed, it was cooled to room temperature, centrifuged, washed and dried to obtain black functionalized carbon nanotubes.

[0055] 2. Preparation of silicone rubber composite materials

[0056] According to the sample formula in Table 1, silicone rubber, white carbon black, wollastonite, low melting point glass powder, hydroxy silicone oil, DCP and functionalized carbon nanotubes were added to the internal mixer in sequence, mixed evenly, pressed into sheets in an open mixer, and vulcanized with a flat vulcanizer under the following conditions: temperature 170°C, pressure 7MPa, time 18min. The vulcanized sample was placed in a muffle furnace and calcined at 1000°C for 1h to prepare a flame-retardant ceramic silicone rubber.

[0057] Table 5 Formula of Sample 7, Sample 8 and Sample 9 (parts by weight)

[0058] Sample name / mass Sample 7 Sample 8 Sample 9 Silicone Rubber 100 100 100 White Carbon Black 40 40 40 Wollastonite 0 30 30 Low melting point glass powder 0 40 40 Hydroxy silicone oil 0 7 7 DCP 1 2 2 Functionalized carbon nanotubes 0 0 5

[0059] The following performance tests were conducted on the rubber composite material: the tensile strength at break and the elongation at break were tested in accordance with GB / T528-2009 and GB / T529-200, respectively; the standard bending strength of the ceramic body was tested in accordance with GB / T 1449-2005; and the limiting oxygen index test was tested in accordance with ASTM D2863. Table 6 shows the limiting oxygen index LOI, ceramic body bending strength, tensile strength at break, and elongation at break of sample 7, sample 8, and sample 9. It can be seen that the silicone rubber composite material prepared by the present invention has excellent flame retardant properties and ceramic properties.

[0060] Table 6 Performance test data of samples 7, 8 and 9

[0061]

[0062] The above embodiments are typical embodiments of the present invention and are not intended to limit the present invention in any way. Any adjustments and modifications to the described technical solutions made by technicians in the technical field shall fall within the protection scope of the present invention as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims.

Claims

1. A flame retardant ceramic silicone rubber, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of silicone rubber, 30-40 parts of white carbon black, 1-2 parts of dicumyl peroxide, 20-30 parts of wollastonite, 30-40 parts of low melting point glass powder, 5-7 parts of hydroxy silicone oil, and 1-5 parts of functionalized carbon nanotubes; The preparation method of the functionalized carbon nanotubes comprises the following steps: firstly, carboxylating the carbon nanotubes to obtain the carboxylated carbon nanotubes; and then forming a complex with the carboxylated carbon nanotubes by doping cobalt and copper ions to obtain the functionalized carbon nanotubes.

2. The flame retardant ceramic silicone rubber according to claim 1, characterized in that: The method for preparing the functionalized carbon nanotubes comprises the following steps: (1) Preparation of carboxylated carbon nanotubes: After the concentrated sulfuric acid and concentrated nitric acid are mixed, the carbon nanotubes are added and ultrasonicated until uniformly dispersed, and then placed in a 100-120°C oil bath for heating and reflux reaction for 12-15 hours; after the reaction, an appropriate amount of deionized water is added for dilution, and a black viscous substance is obtained by centrifugation, and then carboxylated carbon nanotubes are obtained after washing and drying; (2) Preparation of functionalized carbon nanotubes: Sodium phytate and carboxylated carbon nanotubes were dissolved in distilled water by ultrasound, and then a mixed solution of cobalt nitrate hexahydrate and copper nitrate was added, and the mixture was transferred to a reactor and reacted at 200-300°C for 8-12 h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed and dried to obtain functionalized carbon nanotubes.

3. The flame retardant ceramic silicone rubber according to claim 2, characterized in that: In step (1), the mass concentration of concentrated sulfuric acid is 90-98%, the mass concentration of concentrated nitric acid is 60-68%, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1-2:3-4.

4. The flame retardant ceramic silicone rubber according to claim 2, characterized in that: In step (2), the dosage ratio of sodium phytate, carboxylated carbon nanotubes, distilled water, cobalt nitrate hexahydrate and copper nitrate is 4-5 g: 4-5 g: 50-60 mL: 100-120 mL, the total molar amount of cobalt nitrate hexahydrate and copper nitrate in the mixed solution is 26.4 mmol, and the molar ratio of cobalt nitrate hexahydrate to copper nitrate is 1-2: 1-2.

5. The flame retardant ceramic silicone rubber according to claim 1, characterized in that: The silicone rubber is methyl vinyl silicone rubber.

6. A method for preparing the flame retardant ceramic silicone rubber according to any one of claims 1 to 5, characterized in that: Silicone rubber, white carbon black, wollastonite, low-melting-point glass powder, hydroxy silicone oil, diisopropylbenzene peroxide and functionalized carbon nanotubes are added to an internal mixer in sequence, mixed evenly, pressed into sheets in an open mixer, and vulcanized with a flat vulcanizer; the vulcanized sample is placed in a muffle furnace and calcined at 800-1000°C for 1-2 h to make a flame-retardant ceramic silicone rubber.

7. The preparation method according to claim 6, characterized in that The vulcanization conditions are: temperature 170°C, pressure 5-7 MPa, and time 18-25 min.